UPAYA MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SDN TURUSGEDE DI SEMESTER I TAHUN PELAJARAN 2018/2019 DALAM MEMBUKA DAN MENUTUP PEMBELAJARAN MELALUI SUPERVISI AKADEMIK TEKNIK PENILAIAN DIRI SENDIRI - Ulfah, Siti (Widya Wacana: Jurnal Ilmiah, 2019)
The purposes of this reasearch are 1) describing the efforts of increasing the elementary school of Turusgede teachers pedagogic competence at the first semester of 2018/2019 academic year in opening and closing the learning by using the self assessment technique and 2) analysing the increase of the elementary school of Turusgede teachers pedagogic competence at the first semester of 2018/2019 academic year in opening and closing the learning by using the self assessment technique. This research is School Action Research (SAR). This research is taken palce in elementary school of Turusgede, Subdistrict of Rembang, Regency of Rembang. The time of this research is the early-middle first semester of 2018/2019 academic year. The subjects of this research are teachers in the elementary school of Turusgede, Subdistrict of Rembang, Regency of Rembang, consist of twelve teachers. The data of this research is teachers pedagogic competence in opening and closing the learning. The techniques of collecting data are using nontest technique and test technique. The tools of collecting data are using the sheets of observation, camera application on hand phone and the form of self assessment. The technique of analizing data in this research is decriptive comparation. The procedure of this research is using Cycle Model, consist of four steps: planning, action, observation and reflection. Each cycle is going on one week. The results of this research are 1) the academic supervision with self assessment technique is previously sharing the form of self assessment to the subjects of this research, 2) self assessment technique is self assessment according to the next theme and matter, 3) self assessment technique is self assessment after the learning finish and 4) teachers pedagogic competence with self assessment technique is increasing and including good category (B) that according with the result of observation and including very good category (A) that according with the result of self assessment.Â Key words: Pedagogic, Supervision, Self Assessment Technique.